Hoven’s carp Leptobarbus hoevenii strategized metabolism needs to cope with changing environment - Suhaini Mohamad; Sharifah Rahmah; Rabiatul Adawiyyah Zainuddin; Yusnita A Thallib; Ros Suhaida Razali; Mohamad Jalilah; Mazlan Abd Ghaffar; Leong-Seng Lim; Yu Mei Chang; Li Qun Liang; Simon Kumar Das; Young-Mao Chen; et al. (Elsevier Ltd, 2024)
Current water warming and freshwater acidification undoubtedly affect the life of aquatic animals especially ammonotelic teleost by altering their physiological responses. The effect of temperature (28 ◦C vs 32 ◦C) and pH (7 vs. 5) on the metabolic compromising strategies of Hoven’s carp (Leptobarbus hoevenii) was investigated in this study. Fishes were conditioned to (i) 28 ◦C + pH 7 (N28◦C); (ii) 32 ◦C + pH 7 (N32◦C); (iii) 28 ◦C + pH 5 (L28◦C) and (iv) 32 ◦C + pH 5 (L32◦C) for 20 days followed by osmorespiration assay. Results showed that feeding performance of Hoven’s carp was significantly depressed when exposed to low pH conditions (L28◦C and L32◦C). However, by exposed Hoven’s carp to L32◦C induced high metabolic oxygen intake and ammonia excretion to about 2x-folds higher compared to the control group. As for energy mobilization, Hoven’s carp mobilized liver and muscle protein under L28◦C condition. Whereas under high temperature in both pH, Hoven’s carp had the tendency to reserve energy in both of liver and muscle. The findings of this study revealed that Hoven’s carp is sensitive to lower water pH and high temperature, thereby they remodeled their physiological needs to cope with the environmental changes condition.